Strategi Pengendalian Cendawan Fusarium sp. dan Kontaminasi Mikotoksin pada Jagung - Soenartiningsih Soenartiningsih; M. Aqil; N. N. Andayani (Iptek Tanaman Pangan, 2016)
Soil borne fungus Fusarium sp., is a major cause of disease in corn, especially during the rainy season, which causes stem rot disease, ear rot and rotten seeds. The disease symptoms include sudden wilting of leaves, drying stem turns brown in color, and if it reached the ear the seeds will decay. Several species of Fusarium fungus could attack maize, namely F. moniliforme (verticillioides), F. oxysporum, F. proliferatum, F. solani, F. equeseti, F. graminearum. Some soil borne fungal mycotoxins produced by Fusarium sp. are toxic to human and animals such as Zearalenon, Fomonisin, Trikotezen (Deoksinivalenol, Toxin T2) and Moniliformen. Strategy to suppress the infection of Fusarium causing the mycotoxin contamination in maize requires actions, beginning from planting till harvest taking into account several stages of crop management, disease management, use of resistant varieties, disease control using chemical and biological fungicide followed by properly handling the harvest and post-harvest materials and emphasizing the avoidance compound of mycotoxins in the grains.